Mechanical cell disruption of Parachlorella kessleri microalgae: Impact on lipid fraction composition. (May 2018) - Clavijo Rivera, E.; Montalescot, V.; Viau, M.; Drouin, D.; Bourseau, P.; Frappart, M.; Monteux, C.; Couallier, E.
Graphical abstract: Highlights: Disruption increases the quantity of extractable lipids. A large proportion of lipids is recovered in supernatants. Bead milling yields larger droplets, easier to recover. The proportion of free fatty acids increases with disruption. Cell disruption increases the release of amphiphilic substances. Abstract: Samples of nitrogen-starved Parachlorella kessleri containing intact cells (IC), cells ground by bead milling (BM), and cells subjected to high-pressure cell disruption (HPD), together with their supernatants after centrifugation, were compared for granulometry and lipid profiles. The effects of disruption on the lipid profile and organisation were evaluated. The quantity of lipids available for extraction increased with disruption, and up to 81% could be recovered in supernatants after centrifugation, but a marked reorganization occurred. The proportion of amphiphilic free fatty acids and lysophosphatidylcholine increased during disruption due to their release or owing to lipid degradation by enzymes or physical conditions. This effect was more marked in HPD than in BM. Lipids contained in the aqueous phase, after disruption and centrifugation, were enriched in unsaturated fatty acids, BM leading to larger droplets than HPD. The larger liquid lipid droplet would be easier to recover in the following downstream processing.